Construction of Hierarchical Metal–Organic Frameworks by Competitive Coordination Strategy for Highly Efficient CO2 Conversion - Chang, Gang‐Gang; Ma, Xiao‐Chen; Zhang, Yue‐Xing; Wang, Li‐Ying; Tian, Ge; Liu, Jia‐Wen; Wu, Jian; Hu, Zhi‐Yi; Yang, Xiao‐Yu; Chen, Banglin (Advanced materials (Weinheim), 2019)
Hierarchical porosity and functionalization help to fully make use of metal–organic frameworks (MOFs) for their diverse applications. Herein, a simple strategy is reported to construct hierarchically porous MOFs through a competitive coordination method using tetrafluoroborate (M(BF4)x, where M is metal site) as both functional sites and etching agents. The resulting MOFs have in situ formed defect‐mesopores and functional sites without sacrificing their structure stability. The formation mechanism of the defect‐mesopores is elucidated by a combination of experimental and first‐principles calculation method, indicating the general feasibility of this new approach. Compared with the original microporous counterparts, the new hierarchical MOFs exhibit superior adsorption for the bulky dye molecules and catalytic performance for the CO2 conversion attributed to their specific hierarchical pore structures. A simple and novel strategy is reported to fabricate a series of hierarchically porous metal–organic frameworks through the competitive coordination method. The formation mechanism of defect‐mesopores is elucidated by a combination of experimental and first‐principles calculation methods. Furthermore, the adsorption and catalytic advantage over the original microporous counterparts is also demonstrated attributed to their specific hierarchical pore structures.